WOMEN’S PARTICIPATION IN FOREIGN AND DOMESTIC POLICY N THE CONDITIONS OF TRANSFORMATION OF POLITICAL REGIMES - Batrymenko, Oleg; Stychynska, Anna; Tkach, Oleg (Politology bulletin, 2023)
The article highlights the historical formation of the political status of women. The conditions for their inclusion in the political process were characterized and the issue of discrimination against women in politics was investigated. The methodological principles of the study of the women’s issue in politics, taking into account the national specifics, have been determined. The mechanisms of strengthening the political role of women are analyzed. The article attempts to explain the growth of gender norms and feminist strategies in domestic and foreign policy. In order to address these main research questions and stimulate cross-national comparative studies, this article proposes theoretical foundations for defining gender foreign policy. They are based on two directions: international feminist theory and foreign policy analysis. Researchers single out three methods by which a comparative analysis of gender in domestic and foreign policy can be carried out: by distinguishing variations of pro-gender norms and analytical assessment of international trends; by explaining the growth, as well as countering gender norms in foreign policy; by studying the sequence of changes in gender norms to reveal contradictions in foreign policy.

У статті висвітлено історичне становлення політичного статусу жінок. Охарактеризовано умови їх включення до політичного процесу та досліджено питання дискримінації жінок у політиці. Визначено методологічні засади вивчення жіночого питання в політиці з урахуванням національної специфіки. Проаналізовано механізми посилення політичної ролі жінок. У статті здійснюється спроба пояснити зростання ґендерних норм та феміністських стратегій у внутрішній та зовнішній політиці. Для вирішення цих основних дослідницьких питань та стимулювання міжнаціональних порівняльних досліджень, у цій статті пропонуються теоретичні засади визначення ґендерної зовнішньої політики. Вони засновані на двох напрямках: міжнародній феміністській теорії та аналізі зовнішньої політики. Виокремлено три способи, за допомогою яких можна здійснити порівняльний аналіз ґендеру у внутрішній та зовнішній політиці: шляхом виокремлення варіацій проґендерних норм та аналітичної оцінки міжнаціональних тенденцій; шляхом пояснення зростання, а також протидії ґендерним нормам у зовнішній політиці; шляхом вивчення послідовності змін ґендерних норм, щоб виявити суперечності в зовнішній політиці.
УЧАСТЬ ЖІНОК У ЗОВНІШНІЙ ТА ВНУТРІШНІЙ ПОЛІТИЦІ В УМОВАХ ТРАНСФОРМАЦІЙ ПОЛІТИЧНИХ РЕЖИМІВ
Keywords: democracy; representation; political participation; women’s participation; political processes; foreign and domestic policy; state; equality of citizens; political regime; демократія; представництво; політична участь; жіноча участь; політичні процеси; зовнішня і внутрішня політика; держава; рівноправність громадян; політичний режим